Assessing the Impact of the Brent Spar Incident on the Decommissioning Regime in the North East Atlantic - Ole, Ngozi; Faga, Hemen Philip (Faculty of Law, Hasanuddin University, 2017)
The advent of deep-water oil exploration has increased concern for the impact of oil activities on marine environment, especially regarding disused or decommissioned facilities offshore. Before the Brent Spar incident, which galvanised international efforts to protect the environment, international and regional legal instruments on decommissioning of offshore oil installations was weak and ineffective in protecting the environment from the effect of disused facilities. This paper examined the efforts made by international and regional actors to remedy the lapses of the pre-Brent Spar legal instruments on decommissioning of offshore oil facilities, especially regarding the new provisions on environmental protection. The paper concluded that the supplementary legal instruments made post-Brent Spar have not radically transformed the legal regime on decommissioning of offshore oil facilities because contracting states still reserve the discretion to permit abandonment of disused facilities.